Identification Of Soil Transmitted Helminth Using Formol Ether Sedimentation And ZnSO4 Solution Flotation Methods: Identifikasi Soil Transmitted Helminth Menggunakan Metode Sedimentasi Formol Ether Dan Flotasi Larutan ZnSO4 - Taquillah, Naura Silmy; Mahtuti, Erni Yohani; Masyhur, Muhammad; Faisal (Universitas Muhammadiyah Sidoarjo, 2022)
Soil transmitted helminths are parasitic groups of worms that live in countries with subtropical or tropical climates. In humans, when exposed to parasitic eggs or larvae, they can cause infection. Stool examination is divided into qualitative and quantitative examination. Qualitative are direct examination, flotation, tape, deposition, and thick preparations. Kato-Katz and Stoll are quantitative. The purpose of this study was to compare the results of STH identification using the Formol Ether Sedimentation Method and ZnSO4 Solution Flotation with a total sample of 30 samples using purposive sampling. Data analysis with percentage tables and the Chi Square statistical correlation test The results of the analysis prove that the number of samples infected with soil transmitted Helminth with the Formol Ether Sedimentation Method and ZnSO4 solution flotation is the same. With p value = 0.850, which means there is no significant difference between Formol Ether Sedimentation and ZnSO4 solution flotation.